2021
DOI: 10.5811/westjem.2021.2.48430
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Emergency Medicine Clerkship Curriculum during the COVID-19 Pandemic: Development, Application, and Outcomes

Abstract: The COVID-19 pandemic has been a significant catalyst for change in medical education and clinical care. The traditional model of bedside clinical teaching in required advanced clerkships was upended on March 17, 2020, when the Association of American Medical Colleges recommended removing medical students from direct patient care to prevent further spread of the disease and also to help conserve scarce personal protective equipment (PPE). This created unique challenges for delivering a robust, advanced emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 9 publications
0
26
0
1
Order By: Relevance
“…28,31 Outcomes explored were confidence (n= 5), 21,22,24,25,27 competency (n=2) 20,23 and knowledge (n=6). 26,[28][29][30]32,33 Levels of competency, confidence and knot tying and suturing skills were found to have improved across the course of learning and a further study suggested that levels of competency were the same when learning was conducted virtually (2020) compared to in-person pre-COVID (2019). Evidence from RCTs showed that knowledge was greater when learning was conducted using bespoke interactive platforms with a standard video format reported during the COVID pandemic.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…28,31 Outcomes explored were confidence (n= 5), 21,22,24,25,27 competency (n=2) 20,23 and knowledge (n=6). 26,[28][29][30]32,33 Levels of competency, confidence and knot tying and suturing skills were found to have improved across the course of learning and a further study suggested that levels of competency were the same when learning was conducted virtually (2020) compared to in-person pre-COVID (2019). Evidence from RCTs showed that knowledge was greater when learning was conducted using bespoke interactive platforms with a standard video format reported during the COVID pandemic.…”
Section: Resultsmentioning
confidence: 97%
“…Most studies (n=7) were conducted in the USA. 2125,29,33 The remaining studies were conducted in Germany, 26,27,31 Japan, 20 South Korea, 28 Switzerland 32 and Greece. 30…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations